Metagenomic analysis revealing the metabolic role of microbial communities in the free amino acid biosynthesis of Monascus rice vinegar during fermentation - Hang Gao; Jian Zhang; Li Liu; Lijun Fu; Yan Zhao; Germán Mazza; Xin Zhang (Food Science and Human Wellness)
Free amino acid (FAA) is the important component of vinegar that influences quality perception and consumer acceptance. FAA is one of the major metabolites produced by microorganisms; however, the microbial metabolic network on FAA biosynthesis remains unclear. Through metagenomic analysis, this work aimed to elucidate the roles of microbes in FAA biosynthesis during Monascus rice vinegar fermentation. Taxonomic profiles from functional analyses showed 14 dominant genera with high contributions to the metabolism pathways. The metabolic network for FAA biosynthesis was then constructed, and the microbial distribution in different metabolic pathways was illuminated. The results revealed that 5 functional genera were closely involved in FAA biosynthesis. This study illuminated the metabolic roles of microorganisms in FAA biosynthesis and provided crucial insights into the functional attributes of microbiota in vinegar fermentation.